Delayed Diagnosis of Non-ST Segment Elevation Myocardial Infarction in a Young Patient with Multivessel Disease and Familial Hypercholesterolemia Complicated by Cardiogenic Shock Finally Treated with Intra-Aortic Balloon Pump as a Bridge to Extra Corporeal Membrane Oxygenation. (17th January 2019) - Januszek, Rafał; Jędrychowska, Magdalena; Jankowski, Piotr; Dudek, Dariusz; Bartuś, Stanisław
Abstract : Delayed diagnosis of coronary artery disease in young patients after cardiac arrest of unknown origin could increase the risk of death in further diagnostic and therapeutic process. Familial history of premature coronary atherosclerosis and hypercholesterolemia could help in proper diagnosis and treatment. We present a case of a 29-year-old female admitted to the catheterization laboratory with cardiogenic shock and multivessel coronary artery disease treated successfully with multivessel percutaneous coronary intervention and intra-aortic balloon counterpulsation as a bridge to extracorporeal membrane oxygenation.